2011
DOI: 10.1007/s00148-011-0394-4
|View full text |Cite
|
Sign up to set email alerts
|

Lost jobs, broken marriages

Abstract: • ESRC Research Centre on Micro-social Change. Established in 1989 to identify, explain, model and forecast social change in Britain at the individual and household level, the Centre specialises in research using longitudinal data.• ESRC UK Longitudinal Centre. This national resource centre was established in October 1999 to promote the use of longitudinal data and to develop a strategy for the future of large-scale longitudinal surveys. It was responsible for the British Household Panel Survey (BHPS) and for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
93
0
7

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 121 publications
(110 citation statements)
references
References 67 publications
10
93
0
7
Order By: Relevance
“…The interaction term between the attrition dummy and the spousal job loss variable is also statistically insignificant for both genders, thus demonstrating that the cross-partner spillovers that we identify are not disproportionally higher or lower for survey dropouts. 16,17 A related issue arises from the fact that partners may drop from the sample due to divorce or separation, which could be partly induced by the job loss episode (Doiron and Mendolia 2012;Eliason 2012;Hansen 2005;Rege et al 2007). By construction, our sample comprises cohabiting couples, which may be a self-selected sample of all couples experiencing unemployment.…”
Section: Robustness Checksmentioning
confidence: 99%
“…The interaction term between the attrition dummy and the spousal job loss variable is also statistically insignificant for both genders, thus demonstrating that the cross-partner spillovers that we identify are not disproportionally higher or lower for survey dropouts. 16,17 A related issue arises from the fact that partners may drop from the sample due to divorce or separation, which could be partly induced by the job loss episode (Doiron and Mendolia 2012;Eliason 2012;Hansen 2005;Rege et al 2007). By construction, our sample comprises cohabiting couples, which may be a self-selected sample of all couples experiencing unemployment.…”
Section: Robustness Checksmentioning
confidence: 99%
“…It showed that the effect of the Great Recession increased the cost effect of divorce, and in several cases, the loss of job led to the increase of maintenance of one household over two households; this was primarily associated with decline in divorce rate (Artazcoz, Benach, Borrell, & Cortès, 2004). The interpretation of these outcomes points to the meaning of employment being within and beyond the source for income (Eliason, 2012). While in general job losses increase the chances of divorce, the nature of job loss is usually significant in understanding significance of marital dissolution.…”
Section: More Recent Researchmentioning
confidence: 99%
“…Accordingly, marital dissolution results from the decline in husbands' indispensability because their spouses (or perhaps they themselves) consider them to be failing to fulfill the traditional breadwinner role. Support for this thesis is provided by a study from Sweden which finds large risks of divorce after displacement in couples where men lost their jobs but no significant effects if women were displaced (Eliason 2012(Eliason : 1392. Accordingly, if unemployment stigmatizes men more strongly than women in Scandinavian countries where mothers are highly involved in the labor market and often work full-time, we may assume that the effect is even stronger in Switzerland where mothers are less strongly attached to the labor market.…”
Section: Sociabilitymentioning
confidence: 99%